Analysis of the Implementation of Educational Technology in the Teacher Professional Education Program to Enhance Teachers' Digital Literacy at UMS Rappang - Suleha; Yusmah; Aswadi; Jumiati; Muhammad Hanafi; Sam Hermansyah; Erma (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
Digital literacy is an essential skill for teachers in the era of educational digitalization. The Teacher Professional Education (PPG) program at Universitas Muhammadiyah Sidenreng Rappang (UMS Rappang) aims to enhance teachers' competencies by integrating educational technology into the curriculum. This study examines the implementation of educational technology in the PPG program and its impact on improving teachers' digital literacy. The findings indicate that the use of tools such as Learning Management Systems (LMS), video conferencing platforms, educational software, and AR/VR technologies significantly enhances participants' ability to utilize digital tools in teaching. Furthermore, strategies such as intensive training, digital evaluation, and collaborations with technology industries contribute to achieving program goals. However, challenges such as infrastructure limitations, digital competency gaps, and resistance to change require targeted solutions. This study underscores the importance of continuous evaluation and innovation to optimize the integration of educational technology and promote teachers' digital literacy.